Necrotizing Fasciitis of the Anterior Abdominal Wall: A Rare Complication of Neglected Strangulated Richter’s Epigastric Hernia - Seidu, Anwar Sadat; Yenli, Edwin M. T.; Kyereh, Martin; Suoseg, David P.; Yakubu, Musah; Maanikuu, Bernard N.; Batariwah, Gerald; Azure, Emmanuel A. N.; Osman, Imoro; Osman, Haruna Danamiji; Alhassan, Abdul-Latif; Ewura, Abdul Aziz; et al. (International Journal of Innovative Research in Medical Science, 2020)
Necrotizing soft tissue infection (NSTI) is an aggressive and rapidly spreading soft tissue infection that could be associated with high mortality. Early diagnosis can be challenging and so a high index of suspicion is needed. Bedside ultrasonography (USG) and computed tomography (CT) scan could be employed to aid in diagnosis. The objective of this report is to describe the diagnostic process in a resource challenged setting and review the literature. We present an elderly patient with necrotizing fasciitis of the anterior abdominal wall as a complication of neglected strangulated Richter’s epigastric hernia that resulted in mortality.